Screening for Periodontitis during Medical Checkup: A Single Center Cross-sectional Study - Takanori, MATSUURA; Yuto, MUKAIYAMA; Tomonari, SUDA; Kohei, TAKEDA; Yoshiyuki, SASAKI; Daisuke, KIDO; Koji, MIZUTANI; Norihide, TAKAYA; Yuichi, IZUMI; Syujirou, OHTA; Risako, MIKAMI; Takanori, IWATA (The Japanese Journal of Conservative Dentistry, 2020)
Purpose: Recently, a number of studies have revealed that various systemic diseases are associated with periodontitis. In this study, dental data, saliva, serum, and medical data from general medical checkup examinees were examined to explore the relationship between systemic and periodontal conditions and to investigate a new screening system to detect periodontitis based on medical data. Materials and Methods: This study was a cross-sectional, single-center clinical study in Japan, and was conducted from July to August 2015. We performed a periodontal examination on the general medical checkup examinee, and the results of the oral examination and medical checkup were analyzed to clarify the relationship between the systemic status and periodontal condition. To evaluate the periodontal status, we performed a bacteriological examination, by real-time polymerase chain reaction (PCR) using saliva, and a periodontal examination, including measurement of probing pocket depth (PPD), clinical attachment level (CAL), and bleeding on probing (BOP) at six points of all residual teeth by experienced periodontists. For the statistical analysis, multiple regression analysis was performed. Results: Overall, 67 participants (mean age 53.3±1.6 years, 65.7% males) were subjected to data analysis. Mean Body Mass Index (BMI) was 23.36±0.48, and the number of participants who were suffering from diabetes mellitus, cardiovascular disease and chronic kidney disease were 4, 3 and 1, respectively. Thirty-nine participants were non-smokers, 19 were past smokers, and 9 were current smokers. The numbers with periodontal diagnosis of healthy, mild, moderate and severe were 18, 26, 15 and 8, respectively. Multiple logistic regression tests confirmed a statistically significant association between the progression of periodontitis and the number of Porphyromonas gingivalis in saliva, triglyceride level, and bone density after adjustment for age, sex, smoking, BMI, blood pressure, blood glucose, and cholesterol (sensitivity 0.61, specificity 0.95, AUC 0.85). Conclusion: This study showed the possibility that the results of medical checkup and bacteriological examination for P. gingivalis by saliva can be used to screen the progression of periodontitis.